Narrow entrance to the Kudd facing PD’Mello Road - Mumbai Archive Project (Jio Institute, 2024)
The Club of St. Anthony Deussua is located at 351A PD’Mello Road, Mazagaon. The building is not visible from the road, except for the uppermost floor. It is approached through a narrow entrance located between shops facing PD’Mello Road. The road is named after Placid D'Mello (1919–1958), a trade union leader and founder of the All India Port and Dock Workers Federation.